Development of scientific communication at technical university - M. A. Fedorova; A. M. Zavyalov (Moscow Polytechnic University, 2022)
The article focuses on a topical problem of formation researcher's communication skills. This problem is closely connected with the formation of scientific culture, academic writing,both in native language and in English. The authors adhere the position that this problem, especially referring to technical universities, can be solved by modeling the technology for academic skills formation, including academic reading, academic writing and also research speaking. The necessary step is creating at the university scientific environment that ensures scientific communication. This function can be delegated to a special sub-division such as thecentre for research communication development.